Dietary diversity and possible cataract among Chinese elderly population - Zhao, HaiYue; Zhang, Junyang; Zhou, Jie; Ma, Yinghui (Frontiers in Nutrition, 2024)
Background: While cataracts, the vision-clouding eye disease associated with aging, have long presumed dietary underpinnings, the relationship between dietary variety and cataract risk in developing nations has been nebulous. This research aims to investigate the association between dietary diversity scores (DDS) and the risk of cataracts, while considering various dietary diversity patterns.Methods: This research utilized cross-sectional data from 2008 to 2018 extracted from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), implementing the Visual Function Index-14 (VF-14) to gauge cataract probability. The researchers captured participants' diet diversity by using the DDS metric and categorized it into total, animal-based, and plant-based diet patterns. To explore associations between dietary variety and cataract potential, a generalized estimating equation (GEE) was statistically modeled using the data, with adjustments made to account for potentially confounding factors. Additionally, sensitivity analyses were conducted, excluding individuals with assorted eye conditions, to isolate cataract relationships.The study sample comprised 47,395 participants with a mean age of 86.1 years.The study found that a lower likelihood of developing cataract was correlated with both total diet (OR = 0.74; 95% CI: 0.69-0.79) and plant-based diet (OR = 0.65; 95% CI: 0.61-0.71), whereas a slightly higher risk was associated with animal-based diet (OR = 0.90; 95% CI = 0.84-0.96). The results remained unchanged in the sensitivity analysis.The diversified diets are linked to a decreased likelihood of developing cataracts, but animal-based diet faced heightened cataract odds. The implementation of a varied dietary regimen has the potential to serve as a cost-effective and efficient intervention strategy for the prevention of cataracts.